An Asian Theology Of Liberation - Pieris Aloysius (New York Orbis Books, 1988)
Pieris confronts two of the most urgent and complex questions facing Christians today - so many poor people and so many religions. He believes that the approaches of the Christian Churches to these questions will determine whether Christianity will cont
Keywords: Theology - Liberation. Liberation theology. Christianity -- Asia. Christianity and other religions. Asia -- Religion. Catholic Church. RELIGION -- Christianity -- General. RELIGION -- Christian Life -- Social Issues. Christianity. Religion. Asia. Bevrijdingstheologie. Asia -- Catholic Church -- Liberation theology